Investigating the chemical diversity and biomedicinal potential of South African actinomycetes for tuberculosis drug discovery - De Cerf, Christopher (Department of Chemistry, 2019)
The chemical diversity and biomedicinal potential of three South African actinomycetes, Streptomyces speibonae PK-BlueT , Streptomyces africanus CPJVR-H T and Streptomyces pharetrae CZA14T , was investigated. The primary aim was the isolation and structure elucidation of anti-tubercular natural products (NPs), including the re-isolation of the compound named PK-B, reported to be produced by S. speibonae PK-BlueT . Efforts were made to re-isolate the compound named PK-B. However, the results could not be replicated and focus was shifted to the bioassay-guided isolation of antimycobaterial compounds from the three actinobacteria. Culture conditions were optimised for antimycobacterial activity of S. speibonae PK-BlueT extracts by testing against the MTB analogue Mycobacterium aurum A+ (a non-pathogenic, fast-growing mycobacterium that has a similar antibiotic susceptibility to Mycobacterium tuberculosis). Bioactive crude extracts were prioritised for liquid-liquid partitioning and dereplication by LR LC-MS, followed by prefractionation and purification using a combination of HPLC and benchtop column chromatography. Structure elucidation of isolated compounds was achieved using NMR, LCMS and GC-MS data. Bioassays against M. aurum A+ were implemented at every stage of the isolation process to make sure that the isolated compounds had antimycobacterial activity. This strategy led to the isolation of four known compounds, the alkaloid N-phenylpyridin-2- aminium (3.1), a 1:1 mixture of the long-chain fatty acids (LCFAs) n-hexadecanoic acid (3.2) and 14-methylpentadecanoic acid (3.3), and the isoflavone 7-hydroxy-3-(4-hydroxyphenyl)- 4H-chromen-4-one (3.4), from S. speibonae PK-BlueT cultures. Of the four isolated compounds, only 3.1 has not previously been reported from a natural source. The approach of using M. aurum A+ in searching for anti-tubercular compounds was vindicated as 3.1, the mixture of 3.2 and 3.3, and 3.4, in addition to inhibiting the growth of M. aurum A+, exhibited activity against M. tuberculosis H37RvT with MIC90 values of 135 μM, 26 μM and 195 μM, respectively. Additionally, the effect of different growth media on the chemical diversity of S. speibonae PK-BlueT , S. africanus CPJVR-H T and S. pharetrae CZA14T extracts was demonstrated by bioassay where the extracts were screened against a panel of test organisms. HR LC-MS dereplication was used to identify a list of 11 suggested molecular formulae of potentially novel, bioactive NPs in liquid-liquid partitioned extracts of theses three filamentous actinobacteria. Unfortunately, these compounds could not be investigated further due to low biomass and time limitations.